Symbolic violence on social media: Covid-19 and the elderly (Research, Society and Development, 2021)
Objective: To analyze the symbolic violence related to COVID-19 and the elderly on social media. Methods: Qualitative research with a Brazilian case study as investigation strategy. The data collected for analysis were Brazilian memes published on the internet via Instagram social media. Such memes were randomly selected by searching the words “elderly” and “quarantine”. In order to analyze as much material as possible, nineteen memes were selected. Content analysis, as proposed by Bardin, was used to investigate data supported by QSR NVivo® software. Results: Two categories for analysis emerged from the connection observed on the content of the memes selected: the elderly stigmatization and their autonomy denial. Final Considerations: The analysis of the study allowed interpreting that aged people have been constantly experiencing symbolic violence linked to COVID-19 on social media.